Free and fair elections : the constitutional framework in Malaysia - Muhammad Fathi Yusof (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2013)
This research offers critical insight on the concept of free and fair elections and its implementation under the constitutional framework in Malaysia. The study is aimed at analyzing whether the existing constitutional framework has provided enough support on the conduct of free and fair elections. The term 'free and fair elections' is used to describe the standards of election, which are mainly based on international obligations and general democratic principles. The term refers to the principle that supports the fundamental purpose of the election itself. This research explores the concept of free and fair elections based on a mixed academic and applied law research whereby conventional method is used along with historical and evaluative techniques. In this context the quality of elections in Malaysia is measured through assessment on the relevant constitutional provisions. Every element of election in the constitution is examined based on the concept of free and fair election. The findings reveal that, the framers of the Constitution had strongly recommended a reliable system but it has been weakened by the changes proposed by the Working Committee and the amendments afterwards. The result of this thesis also shows that the existing electoral process is partially free and fair. The facts that the political freedoms are curtailed, the restrictions on political critics and the failure to ratify international instruments are among the basis of the finding that the election is partially free. The conclusion that the Malaysia election is not completely fair is based on the many indicators such as: degree of neutrality the Election Commission; lack of caretaker government policy; unfair media access; and unfair delimitation. The study proposes a genuine electoral reform which should start with administrative reform. This research also strongly argues on the importance of fair competition, transparency, accountability and control on political party financing. The result obtained may assist in providing academic perspective for electoral reform. More importantly, it would be very helpful for more detailed research of essential areas on elections in order to improve the electoral process in Malaysia.